Mutations in STAG2 cause an X‐linked cohesinopathy associated with undergrowth, developmental delay, and dysmorphia: Expanding the phenotype in males. Issue 2 (16th November 2018) - Mullegama, Sureni V.; Klein, Steven D.; Signer, Rebecca H.; ,; Vilain, Eric; Martinez‐Agosto, Julian A.
Abstract: Background: The cohesin complex is a multi‐subunit protein complex which regulates sister chromatid cohesion and separation during cellular division. In addition, this evolutionarily conserved protein complex plays an integral role in DNA replication, DNA repair, and the regulation of transcription. The core complex is composed of four subunits: RAD21, SMC1A, SMC3, and STAG1/2. Mutations in these proteins have been implicated in human developmental disorders collectively termed "cohesinopathies." Methods: Using clinical exome sequencing, we have previously identified three female cases with heterozygous STAG2 mutations and overlapping syndromic phenotypes. Subsequently, a familial missense variant was identified in five male family members. Results: We now present the case of a 4‐year‐old male with developmental delay, failure to thrive, short stature, and polydactyly with a likely pathogenic STAG2 de novo missense hemizygous variant, c.3027A>T, p.Lys1009Asn. Furthermore, we compare the phenotypes of the four previously reported STAG2 variants with our case. Conclusion: We conclude that mutations in STAG2 cause a novel constellation of sex‐specific cohesinopathy‐related phenotypes and are furthermore, essential for neurodevelopment, human growth, and behavioral development. Abstract : We present the case of a 4‐year‐old male with developmental delay, failure to thrive, short stature, and polydactyly with a likely pathogenic STAG2 de novo missense hemizygous variant, c.3027A>T, p.Lys1009Asn. We believe that mutations in STAG2 cause a novel constellation of sex‐specific cohesinopathy‐related phenotypes and are furthermore essential for neurodevelopment, human growth, and behavioral development.